Design Principles for Compact, Backdrivable Actuation in Partial-Assist Powered Knee Orthoses - Zhu, Hanqi; Nesler, Christopher; Divekar, Nikhil; Peddinti, Vamsi; Gregg, Robert D. (IEEE/ASME transactions on mechatronics, 2021)
This article presents the design and validation of a backdrivable powered knee orthosis for partial assistance of lower-limb musculature, which aims to facilitate daily activities in individuals with musculoskeletal disorders. The actuator design is guided by design principles that prioritize backdrivability, output torque, and compactness. First, we show that increasing the motor diameter while reducing the gear ratio for a fixed output torque ultimately reduces the reflected inertia (and thus backdrive torque). We also identify a tradeoff with actuator torque density that can be addressed by improving the motor's thermal environment, motivating our design of a custom brushless dc motor with encapsulated windings. Finally, by designing a 7:1 planetary gearset directly into the stator, the actuator has a high package factor that reduces size and weight. Benchtop tests verify that the custom actuator can produce at least 23.9-N \,·\, m peak torque and 12.78-N \,·\, m continuous torque, yet has less than 2.68-N \,·\, m backdrive torque during walking conditions. Able-bodied human subject experiments ( N=3 ) demonstrate reduced quadricep activation with bilateral orthosis assistance during lifting-lowering, sit-to-stand, and stair climbing. The minimal transmission also produces negligible acoustic noise.